The Role Of Advocates In Accompanying Children In Conflict With The Law In The Diversion Process - Fauziah Lubis; Madinah Asri Putri Andarin; Isro Ayu Marbun; Khairunnisa Harahap; Rabiatul Adawiyah Siregar; Sarmila Munthe (SEAN Institute, 2025)
One of the from Lots challenges faced moment This in use diversion in the judicial process child is capacity advocate For understand and apply concepts In the research This, using normative methods with approach one approach, especially Constitution Number 11 of 2012 which regulates System Justice Child Criminal Act. According to results research, advocate hold role important in the process of diversion for troubled children with law Because they ensure that rights child is upheld, proposed non- criminal settlement that emphasizes rehabilitation, as well as give consultation about rights and options available solutions. They push implementation principle justice restorative with involving all party in taking decision For reach peace, while act as a professional independent representative. However, even though role this is very important, advocate face various challenges, including lack of understanding about draft diversion, discontinuity regulation, inequality power in mediation, as well as obstacle cultural and social. Limitations source power and resistance from apparatus enforcer the law also makes things worse situation. Challenges This need addressed so that advocates can give mentoring more laws effective and quality for child in conflict with law.